Effect of IT Application on Project Performance Focusing on the Mediating Role of Organizational Innovation, Knowledge Management and Organizational Capabilities - Hemmati, M.; Hosseini, H. (Engineering, Technology & Applied Science Research, 2016)
The purpose of this study is to examine the effect of IT application on project performance focusing on mediating role of organizational innovation, knowledge management and organizational capabilities using SEM. For this purpose, 194 managers, supervisors and experts of software developer companies participated in this study. Participants were asked to complete a questionnaire on each subject. SEM was used to analyze data using the LISREL software. Results are thoroughly discussed in this paper and the findings support the role of IT application, organizational innovation, knowledge management and organizational capabilities on project performance and project benefits.